(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The present study is an attempt to portray the behavior of the consumers after the purchase of consumer durable goods in Chittoor District. The satisfaction level of consumers is very important because if they are satisfied with the product, then they will repeat the purchase, which in turn leads to increasing the profitability of the company. Hence, the researcher has taken the present study in order to know the behavioral pattern of the consumers after the purchase of consumer durable goods. The sample size of the respondents is 250, and the researcher has used a simple random sampling technique for collecting the first-hand information from the consumers. The sampling units are rural and urban areas of Chittoor District (i.e., Srikalahasthi, Renigunta, Tirupati, and Cherlopalli).